Squamous Cell Carcinoma Arising in a Mature Cystic Teratoma. (23rd December 2012) - Avcı, Suna; Selcukbiricik, Fatih; Bilici, Ahmet; Özkan, Gülkan; Özağarı, Ayse Ayşim; Borlu, Fatih
Abstract : Introduction . Malignant transformation in a mature cystic teratoma of the ovary is a rare complication. Squamous cell carcinoma is the most common transformation. We describe a new case of squamous cell carcinoma arising in a mature cystic teratoma. Case Report . A premenopausal 52-year-old female patient is diagnosed with vaginal bleeding. According to examination made on the women and the pelvic scanning, 7 cm mass is found on the right adnexa of the patient. Total abdominal hysterectomy, bilateral salpingo-oophorectomy, omentectomy, pelvic lymph node dissection, and debulking were the treatments completed on the patient. According to histopathological diagnosis, squamous cell carcinoma arising in a mature cystic teratoma is diagnosed as a reason for the mass in the right adnexa of the patient. Conclusion . The prognosis of the malign transformation of MCT depends on surgery stage; however it is extremely poor. The patient should receive chemotherapy regardless of stage. We have decided to administer second cycle carboplatin and paclitaxel treatments on the patient.